2020
DOI: 10.48084/etasr.3750
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of the Synthesized Iron-Carbide Mixture on the Adhesive and Mechanical Properties of Epoxy Composites for Parts of Transport Machines

Abstract: Epoxy-diane oligomer ED-20, hardener polyethylene polyamine, and micro dispersed particles of iron-carbide mixture synthesized by high-voltage electric discharge have been used for the formation of Composite Materials (CMs) and protective coatings for the transport industry. The dependence of the adhesive, physical, and mechanical properties and residual stresses of epoxy composites on the content of micro dispersed powders has been studied in this paper. It has been proved that for the formation of a composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Figure 1 shows the elasto-plastic stress-strain curve behavior of the steel. Such materials are characterized by increased mechanical strength and the ability to resist static and shock [11]. The mechanical characteristics (Table I) of the base metal such as yield strength σe, ultimate tensile strength σu, deformation ε, and Young's modulus E were obtained from the curve in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the elasto-plastic stress-strain curve behavior of the steel. Such materials are characterized by increased mechanical strength and the ability to resist static and shock [11]. The mechanical characteristics (Table I) of the base metal such as yield strength σe, ultimate tensile strength σu, deformation ε, and Young's modulus E were obtained from the curve in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…We notice that the optimal results are for the tightening torques of 25 and 30Nm. This is because the tightening torque mainly influences the elastic phase before sliding and the maximum level of load [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The tightening torque has been correctly introduced by applying local compression to the substrate and by pulling the bolt, thus allowing the prestressing forces to be introduced into the substrates [17].…”
Section: B Influence Of Torquementioning
confidence: 99%
“…The authors [10][11][12][13][14][15] have demonstrated that using polymer CMs substantially enhances the physical and mechanical properties and the wear resistance of transportation components exposed to aggressive environments. Consequently, this significantly extends the service life of mechanisms and machines, contributing to their reliability [16][17][18][19][20]. Based on these findings, it can be affirmed that the investigation of the effects of static loads on the alteration of the physical and mechanical properties of materials during operation, while considering environmental safety concerns, stands as a critical objective in contemporary polymer materials science.…”
Section: Introductionmentioning
confidence: 91%
“…However, zinc phosphate is a scarce material compared to chromate [15,16]. At the same time, it has been proven [17][18][19] that the use of nitrites can prevent the pitting corrosion of steel. Compared to other heavy metal corrosion ions-05025-2 inhibitors, such as (CrO4 2 − , WO4 2 − , MoO4 2 − , Cr2O7 2 ), nitrites have less negative environmental impact.…”
Section: Introductionmentioning
confidence: 99%